Association Between Use of Statins and Survival After Stroke: Real-World Data from The Australian Stroke Clinical Registry - Dalli, Lachlan L; Kim, Joosup; Cadilhac, Dominique A; Andrew, Nadine E; Sanfilippo, Frank M; Thrift, Amanda G; Sundararajan, Vijaya; Kilkenny, Monique F (International Journal of Population Data Science, 2020)
Introduction Despite being recommended in clinical guidelines for secondary prevention of stroke, there are limited real-world data on outcomes associated with use of statins post-stroke. Objectives and Approach We aimed to investigate the association between statin use and cardiovascular mortality post-stroke. We conducted a retrospective cohort study using prospectively collected data from the Australian Stroke Clinical Registry (2010-2014), linked with national medication dispensing and mortality data. We observed adult patients with first-ever ischaemic stroke or transient ischaemic attack (TIA) for 1-year following hospital discharge, or until their date of death, whichever occurred first. Statin use, defined as having an available statin dispensing, was assessed daily and treated as a time-varying exposure to account for patients who discontinued or reinitiated statins during follow-up. Multivariable, competing-risks regression, with non-cardiovascular death as the competing risk, was used to investigate the association between statin use and 1-year cardiovascular mortality. Results Among 8363 patients discharged following first-ever ischaemic stroke or TIA (48% aged ≥75 years, 45% female, 20% TIA, median length-of-stay 5 days), 945 died within 1 year, with 763 deaths being cardiovascular-related. The proportion of statin users was 65% at 90 days, 64% at 180 days, and 62% at 1 year. Groups least likely to be statin users at 1-year were women (odds ratio [OR]: 0.75; 95% CI: 0.67-0.85), patients aged <65 years (OR: 0.80; 95% CI: 0.69-0.92), and those discharged directly home (OR: 0.77; 95% CI: 0.67-0.88). Compared to non-use, use of statins was associated with a reduced risk of cardiovascular mortality within 1 year overall (sub-distribution hazard ratio [SHR]: 0.40; 95% CI: 0.34-0.46), and in sub-groups of patients with TIA, severe stroke, and advanced age. Conclusion / Implications: Our preliminary data provide evidence of survival benefits associated with post-stroke statin use. Interventions to improve medication adherence may assist in reducing post-stroke mortality.